2017
DOI: 10.1080/0142159x.2017.1324140
|View full text |Cite
|
Sign up to set email alerts
|

Twelve tips for effective body language for medical educators

Abstract: Medical educators seeking to maximize their effectiveness would benefit from an understanding of how body language affects a learning environment and how body language techniques can be used to engage audiences, maintain attention, control challenging learners, and convey passion for a topic. Understanding and using body language effectively is an important instructional skill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 32 publications
1
22
0
2
Order By: Relevance
“…If possible, step from behind a podium and move about the room to maintain audience attention and connection as equally as possible regardless of their location (Roediger et al, 2011); avoid pacing or other distracting motions. Incorporate these tips while maintaining authenticity in your personal style and in the situation (Hale et al, 2017).…”
Section: Tip 8: Promote Input From All Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…If possible, step from behind a podium and move about the room to maintain audience attention and connection as equally as possible regardless of their location (Roediger et al, 2011); avoid pacing or other distracting motions. Incorporate these tips while maintaining authenticity in your personal style and in the situation (Hale et al, 2017).…”
Section: Tip 8: Promote Input From All Studentsmentioning
confidence: 99%
“…or verbally ("I'm curious what the rest of you think", "let's save that topic for after class so we can return to the question at hand", etc.) (Hale et al, 2017).…”
Section: Tip 8: Promote Input From All Studentsmentioning
confidence: 99%
“…4 NVC is an important skill needed for the teachers while they are interacting to large group of students because it effects positively on student's mood. 1 NVC is the behavior of the face, body, or voice 2,5 and is divided into; kinesics (body postures and body movements), vocalics (non-linguistic vocal cues such as volume and sound pitch), oculesics (gaze and movement of eye), haptics (body contact such as handshakes) and proxemics (personal space and distance). 4 The word kinesics refers to the study of hand, arm, body, and face movements.…”
Section: Introductionmentioning
confidence: 99%
“…A well-recognized study reported the significance of nonverbal communication, which leads to the "7/38/55" rule, where 7% of communication originates from spoken words, while 38% comes from the tone of the voice and 55% from our body language. So, educators can benefit from body language which engages the audience, grabs attention, controls challenging learners and conveys passion for a topic (46).…”
Section: Discussionmentioning
confidence: 99%